2010
DOI: 10.1021/jp908395v
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Behavior of ZnFe2O4 Nanoparticles: Effects of a Solid Matrix and the Particle Size

Abstract: ZnFe 2 O 4 nanoparticles with sizes between 3 and 20 nm have been prepared nonembedded and embedded in an amorphous SiO 2 matrix. All the samples are ferrimagnetic below the blocking temperature that presents similar values for all of them, indicated by the maxima in the ZFC/FC curves. However, the embedded nanoparticles with sizes between 3 and 7 nm present much higher values of coercive field than the nonembedded particles. The fact that particles with different sizes present similar blocking temperature val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 39 publications
2
81
1
Order By: Relevance
“…To discuss the variation of the coercivities in ZFO-50 and ZFO-70, the magnetic domain dependence on the nanoparticle size should be considered. It has been reported that ferrite nanoparticles usually transfer from multi-domains to a single domain state when the particle size was decreased below the critical diameter of 15-18 nm [22]. In the multi-domain state, the surface effects can lead to large anisotropy energy in nanoparticles due to the uncompensated surface spin [1].…”
Section: Resultsmentioning
confidence: 99%
“…To discuss the variation of the coercivities in ZFO-50 and ZFO-70, the magnetic domain dependence on the nanoparticle size should be considered. It has been reported that ferrite nanoparticles usually transfer from multi-domains to a single domain state when the particle size was decreased below the critical diameter of 15-18 nm [22]. In the multi-domain state, the surface effects can lead to large anisotropy energy in nanoparticles due to the uncompensated surface spin [1].…”
Section: Resultsmentioning
confidence: 99%
“…This leads to the observed narrowing of the resonance line and an internal magnetic field averaging out to zero with temperature increase. The value of T B for ferrite nanoparticles depends on the particle sizes, synthesis conditions, and applied magnetic field [20,21]. For ZFO nanoparticles with a mean size of ∼11 nm, the reported values of T B were in a wide 21−150 K temperature range [21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of a diffraction pattern at a particular Bragg angle depends on the number of scattering centers in the medium. All the reported works regarding X-ray analysis of ferrite/silica composites treated the SiO 2 matrix as amorphous [9][10][11][12][13][14][15][16][17][18][19][20]. Hence, the intensity of the X-ray at any Bragg angle is contributed by both the ferrite phase and the background amorphous medium.…”
Section: Xrd Analysismentioning
confidence: 99%
“…There are several studies on the effect of the silica matrix on the structural and magnetic properties of NZFO [10,11,[13][14][15], ZFO [16,17], and NFO [18,19] by changing the ferrite content in SiO 2 . It is found that the amorphous medium has a strong influence on the size of ferrite crystallites and their magnetic properties.…”
Section: Introductionmentioning
confidence: 99%